Antimicrobial role of glycosaminoglycan’s: beyond bacterial adhesion to host cell - Urbi, Zannat; Nina Suhaity, Azmi; Hossain, Md. Sanower (MDPI, 2021)
Glycosaminoglycans (GAGs) are complex unbranched polysaccharides widely found in intracellular compartments, at the cell surface, and in the extracellular environment in living organisms. This availability facilitates attachment of a wide variety of microbial pathogens, including viruses, bacteria, parasites, and fungi, to the host cells and invasion or evasion of host defence mechanisms. There are no doubt GAGs has a potential role in pathogenesis in infectious diseases, and at the same time, GAGs have multiple applications in the medical, veterinary, pharmaceutical, and cosmetic fields. However, little is known about the mechanistic role of GAGs as therapeutic agents, particularly antimicrobial agents. Several documented literature reported primary findings of the antibacterial, antiviral and antiparasitic role of GAGs in controlling infections. Heparin, one kind of GAGs, can prevent biofilm formation for a more extended period in ureteral stents. Desulfated heparins also reduced bacterial adhesion to different extents depending on the bacterium and the sulfated residue. Are GAGs valuable agents for the treatment of infectious diseases or only facilitator of the pathogenesis of infections? This perspective study aims to discuss the current understanding of how microbes co-opt GAGs activities to bypass host defence mechanisms and to propose the reverse role of GAGS as antimicrobial agents for the inhibition of infections or treatment of infectious diseases by considering the contributing mechanisms to the anti-infective pharmacology of GAGs alone or GAGs-based experimental studies.